PENGGALIAN DAN INTERNALISASI CORE VALUES CHAMPION PADA PROSES PEMBELAJARAN MANAJEMEN SUMBER DAYA MANUSIA - Micheline Rinamurti; Heri Setiawan Setiawan (Catholic University Musi Charitas, 2018)
This study aims to obtain concrete examples of learning outcomes based on the internalization of the synergy between the core values of Catholic University of Musi Charitas (i.e. CHAMPION) and the KKNI module (i.e Human Resource Management or HRM) in the Management in the Management Study Program. CHAMPION's core values are Charity, Humanity, Altruism, Managing-capacity, Persistence, Integrity, Open-minded, and Novelty. Internalizing the core values of CHAMPION in the semester learning plan for HRM courses will provide the characteristic that distinguishes them from other universities. The application of HRM which is synergized with the core values of CHAMPION is is likely to produce human resources management from to produce management of human resources from the teaching and learning process that is systemic, holistic, interdisciplinary and participatory. Based on the results of the study, it has an impact on learning outcomes; attitudes and values are 29.58%, general skills are 14.79%, special skills are 33.80%, and mastery of knowledge is 21.83%. Three very interesting learning methods are; Student centered learning is 39.47%, group interaction / discussion is 32.89%, and project-based learning is 27.63%. Learning experience; the task is 29%, composing papers is 27%, practicing is 20%, surveys or visits are 16%, and comparative studies are 8%. Assessment criteria / rubric; Assignment tests as courses, projects, portfolios are 35.9%, written tests are 30.9%, , performance tests are 16.9%, observation tests are 7%, and participation tests are 2.8%.. Based on the aforementioned data, the Semester Learning Plan is designed for Human Resource Management based on CHAMPION core values.